High Varus Angle and Lower Posterior Tibial Slope Associated with PCL Injury in Cruciate Retaining Total Knee Arthroplasty: An MRI Study - Çabuk, Haluk; İmren, Yunus; Tekin, Ali Çağrı; Dedeoğlu, Süleyman Semih; Gürbüz, Hakan (The Journal of Knee Surgery, 2018)
The posterior tibial slope (PTS) is important for performing a tibial cut that does not injure the posterior cruciate ligament (PCL). In this study, the amount of PCL fibers sacrificed under simulated tibial cuts with varying posterior inclinations was evaluated using magnetic resonance images (MRIs) of osteoarthritic varus knees. Knee X-rays, orthoroentgenograms, and MRIs of 113 Kellgren and Lawrence grades 3 to 4 osteoarthritic knees were included. Four different simulated tibial cuts were performed at 0, 3, 5 degrees and parallel to the tibia plateau 3 mm below of the most defective part of the cartilage in the medial plateau. Correlations between the PCL avulsion amount and the PTS and varus alignment of the lower extremity were analyzed for all four simulated tibial cut levels. The maximum amount of PCL was preserved with a 0-degree tibial cut in patients with a PTS of more than 8 degrees. With increased tibial cut angles, the posterior slope resulted in an increased amount of avulsed PCL. Although the amount of avulsed PCL was proportional with the varus alignment, it was inversely proportional with the sagittal slope. The number of injured PCLs also increased as the slope of the tibial cuts increased. Patients with mild varus alignments and high PTSs are more suitable for cruciate retaining total knee arthroplasty.
Keywords: total knee arthroplasty; posterior cruciate ligament; cruciate retaining total knee arthroplasty; tibial cut; magnetic resonance; knee osteoarthritis